Bentuk Dukungan Puskesmas Sebagai Upaya Pencegahan Penularan HIV AIDS Terhadap Wanita Pekerja Seksual - Tampubolon, Rifatolistia (Politeknik Kesehatan Tanjungkarang, 2018)
Human Immuno-deficiency Virus (HIV) is a virus that affects the immune system and causes Acquired Immunodeficiency Syndrom (AIDS). In 2014, new cases of HIV in Indonesia reached 32.711 cases and increased to 41.250 cases in 2016. One of many groups that tend to be infected with HIV was commercial sex workers. This study was to describe kinds of support from Primary Health Care Service in preventing sexually transmitted diseases and decreasing the transmission of HIV AIDS to commercial sex workers. This study was a qualitative research using phenomenological approach. Seven participants were involved, consist of five commercial sex workers, one procurer, and one of a health worker as informants. Data were collected using the in-depth interview. This study was done in Sexually Transmitted Infection Clinic in Gambilangu localization. The result of the study showed the kinds of support in preventing HIV AIDS transmission were routine screening, delivery of condoms and medications, and sustainable education to commercial sex workers. There was an obstacle in performing the support, such as no policies for the consumer to wear a condom. Therefore, the government and community should be involved in implementing the policies as an effort to prevent HIV AIDS transmission.